Origin and Dissemination of Altered El Tor Vibrio cholerae O1 Causing Cholera in Odisha, India: Two and Half Decade’s View - Pal, Bibhuti Bhusan; Behera, Dipti Ranjan; Nayak, Smruti Ranjan; Nayak, Ashish Kumar (Frontiers in Microbiology, 2021)
The origin, spread and molecular epidemiology of altered El Tor Vibrio cholerae O1 strains isolated from cholera outbreaks/surveillance studies between 1995 to 2019 from different district of Odisha were analysed. The stock cultures of Vibrio cholerae O1 strains from 1995 to 2019 were analysed through molecular analysis using different PCR assays and Pulse field gel electrophoresis (PFGE) analysis. The spread map (month, year and place) was constructed to locate the dissemination of altered El Tor variants of V. cholerae O1 in this region. A total of 13 cholera outbreaks were caused by Vibrio cholerae O1 Ogawa biotype El Tor carrying ctxB1 and ctxB7 genotypes. The ctxB1 alleles of V. cholerae O1 mostly confined to the coastal areas; whereas the ctxB7 genotypes though originated in the coastal region of Odisha concentrated more in the tribal areas. The positive correlation between virulence associated genes (VAGs) was found through Pearson’s correlation model indicative of stronger association between the VAGs. Clonal relationship through PFGE between ctxB1 and ctxB7 genotypes of V. cholerae O1 strains exhibited 80% similarity indicating single or multi-clonal evolution. It is evident from this study that the spread of multidrug resistant V. cholerae O1 altered El Tor was dominant over the prototype El tor strains in this region. The origin of altered El Tor variants of V. cholerae O1 occurred in the East Coast of Odisha established that the origin of cholera happened in the Gangetic belts of Bay of Bengal where all new variants of V. cholerae O1 might have originated from the Asian countries.